MAGNETOSPHERIC ACCRETION IN T TAURI STARS: OBSERVATIONAL TEST - Petrov, P. P. (Одеські астрономічні публікації, 2017)
In the classical T Tauri stars (CTTS) the magnetic field plays an important role in the interaction between the star and the accretion disk. In 1996-2000 we have carried out an extensive spectroscopic and photometric monitoring of the extremly active CTTS RW Aur A in order to check for predictions of the magnetospheric accretion model. We find periodic rotational modulations in many spectral features, which may be explained as due to non-axisymmetric accretion, well in accordance with the model. The stable period (2.d 64) was also found in the variations of the blue colours. Nevertheless, some of the important predictions of the model were not found in the star.